Awareness on Breast Cancer among the Women of Reproductive Age - Shahanaz Chowdhury; Shaila Sultana (Tehran University of Medical Sciences, 2011)
Objective: To assess the level of awareness on breast cancer among women of reproductive age. Materials and methods: A cross-sectional descriptive study was conducted in OPD of Dhaka Medical College Hospital among the 175 respondents by face to face interview using pretested semi structured questionnaire. Results: One forth (23%) aged 21-25 years, mostly Muslim (86.3%), housewives (72.57%), had children (81.05%) and live in urban (69%) area. One third of them were illiterate and married at 16-20 years. Slightly less than half of their family income was taka 4500 to 5500. Six of 10 respondents (64%) knew that it was common cancer in women and almost all (94.29%) mentioned that breast cancer did not occur in old age. In addition half of them said that it was not inherited, signs and symptoms of breast cancer was spontaneous clear or bloody discharge from nipple often associated with a lump (61.14%), and it could not be cured (54.3%). Majority of them (78.9%) did not know that early diagnosis improves treatment outcome and the risk factor of breast cancer (65.14%). Half of them (57.5%) had knowledge that clinical breast examination as screening method of breast cancer but vast majority did not practice clinical breast examination. Only 16.67% of the respondents did BSE regularly and among them 83.33% did not know the best time for breast self examination. Practice breast feeding was universal among them but for less than 6 months. Conclusion:The study found that women were not so much aware regarding breast cancer and also preventive measures, risk factors so on. So for better awareness, campaign and counseling program from both Government and NGOs is needed.